Prevalence rate of ecto and endoparasities infestation in Javan Mynas - Roslam, Nik Nur Siti Syafura (2015)
Myna spp are well recognized in the country as introduced pests having potential harm to human health, crop damage and competing with native wildlife. This study was undertaken to evaluate the prevalence rate of ectoparasites and endoparasites in Javan Mynas. A total 19 birds of Javan Mynas were captured from the wild in Banting, Selangor using a mist net. The measurements taken were body weight, size of bill, head, body, wing, tarsus, and tail. The infestation rate of three species of ectoparasites were lice Felicola sp 21%, Myrsidea 79%, and mite Falculifer rostratus 79%. Two species of endoparasites were found from the post mortem procedure, nematode Diplotriaena sp 53% and Pelecitus sp 21%. There was no significant correlation between numbers of ectoparasites and endoparasites counted in Javan Mynas. This shows that if there was a higher infestation of ectoparasites, it does not necessarily result in a higher infestation of endoparasites. Javan Mynas in Malaysia are proven to be carriers of many species of ectoparasites and endoparasites.